2015
DOI: 10.30552/ejep.v7i1.98
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences on tests of crystallized intelligence

Abstract: This study aimed to determine whether performance on tests of crystallized intelligence is affected by gender and to ascertain whether differential item parameters could account for the gender disparities. The sample comprised 1.191 individuals (55% women) between the ages of 16 and 77 years old (M=22; SD=9.5). The participants were primarily college students (58.3%) living in four Brazilian states. Four verbal tests measuring crystallized intelligence (vocabulary, synonyms, antonyms and verbal analogies) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There are also DIF analysis studies conducted with the selected sample groups of commonly used intelligence tests. Wechsler et al, (2014) applied four verbal tests to 1191 participants in their studies, in which they investigated gender-based DIF in crystallized intelligence using Rasch model. No significant gender-related difference was obtained in the total scores.…”
Section: Dif In Intelligence Scalesmentioning
confidence: 99%
“…There are also DIF analysis studies conducted with the selected sample groups of commonly used intelligence tests. Wechsler et al, (2014) applied four verbal tests to 1191 participants in their studies, in which they investigated gender-based DIF in crystallized intelligence using Rasch model. No significant gender-related difference was obtained in the total scores.…”
Section: Dif In Intelligence Scalesmentioning
confidence: 99%
“…In addition, the psychological well-being of high intellectually able individuals has been a controversial topic in the specialized literature; sometimes it has been considered that they are more prone to psychological maladjustments, while other researchers present inconclusive evidences about this issue [25]. Nonetheless, the results of the diverse studies [26][27][28][29], have shown that there is not always a direct relationship between the construct intellectual ability and the levels of socioemotional adjustment and psychological well-being [30].…”
Section: High Ability Adolescents and Their Psychological Well-beingmentioning
confidence: 99%
“…The study of gender differences in intelligence scores has been a significant issue since the pioneering studies of Terman (1916) in the study of intelligence. Researchers have examined gender differences in intelligence mainly by comparing factor and subtest scores (Colom et al, 2004; Irwing & Lynn, 2005; Reis & Park, 2001; Wechsler et al, 2014). Some studies yielded insignificant differences between males and females in general intelligence scores, whereas others showed gender differences (Irwing & Lynn, 2005; Jackson & Rushton, 2006; Nyborg, 2003).…”
Section: Introductionmentioning
confidence: 99%